Exploration on pavement surface conditions attributed to Mineral freight and logistics operations on kuantan road Network - A., Ismail; M. R., Intan Suhana; K. A., Masri; Rapar, N. H. (2019)
The most active mineral mining operations in Malaysia are located in Kuantan, Pahang. The rapid increases of the minerals operations are of concern due to its significant impacts on the environment and human health. While effects to the environment and human health are a great of concern, the effect to the transportation system also should not be neglected. With the continuous growth of these industries, there will be more heavy vehicles generated on road transporting minerals related products leading to several issues especially on road pavement damages. Pavement damages are always associated with its optimum function and may contribute to road crashes. There are several factors that influenced the pavement damages such as weather changes, quality of material use, improper maintenance and traffic operations. This study was conducted to explore the pavement damages occurrence based on traffic operation which focusing on heavy vehicles composition as centre for critical analysis. To achieve this study, the identification of regular routing used for minerals logistic operation from the mining source to the port was chosen as study location. This study was conducted by using visual observation survey and traffic volume survey. A set of historical data on route inspection supplied by Road Care also been used for analysis. Then, data obtained were analyzed using road disability level and road rating assessment. The result shows that the road rating leading to Kuantan Port was less satisfactory (rating C) with the marks of 7.27 and the highest type of damage found was cracking with 36% followed by rutting (33%) and potholes (31%). The outcomes from this study were hoped to bring some understanding on the impact of heavy vehicles towards transportation system within a local road network in Kuantan.